2022
DOI: 10.1212/wnl.0000000000012969
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Damage and Its Clinical Correlates in People With Early Huntington Disease

Abstract: Background and ObjectivesSynaptic damage has been proposed to play a major role in the pathophysiology of Huntington disease (HD), but in vivo evidence in humans is lacking. We performed a PET imaging study to assess synaptic damage and its clinical correlates in early HD in vivo.MethodsIn this cross-sectional study, premanifest and early manifest (Shoulson-Fahn stage 1 and 2) HD mutation carriers and age- and sex-matched healthy controls underwent clinical assessment of motor and nonmotor manifestations and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 49 publications
(115 reference statements)
7
54
0
Order By: Relevance
“…A study of patients with premanifest and early Huntington’s disease revealed reduced [ 11 C]UCB-J binding in putamen, caudate, pallidum, cerebellum, and parietal, temporal, and frontal cortices of the patients. Comparative analyses with [ 18 F]-FDG revealed reduced metabolism only in putamen and caudate ( Delva et al, 2021 ).…”
Section: Synaptic Vesicle Glycoprotein 2a and Positron Emission Tomog...mentioning
confidence: 99%
“…A study of patients with premanifest and early Huntington’s disease revealed reduced [ 11 C]UCB-J binding in putamen, caudate, pallidum, cerebellum, and parietal, temporal, and frontal cortices of the patients. Comparative analyses with [ 18 F]-FDG revealed reduced metabolism only in putamen and caudate ( Delva et al, 2021 ).…”
Section: Synaptic Vesicle Glycoprotein 2a and Positron Emission Tomog...mentioning
confidence: 99%
“…Loss of From Pathophysiology to Treatment of Huntington's Disease SV2A in the putamen correlated with the TMS. In premanifest HDEGC there was only significant decrease in SVA2 in the caudate and putamen [57].…”
Section: Pet-scanmentioning
confidence: 79%
“…One recent imaging study using both PET and MRI, found significant volume loss in caudate, putamen, and pallidum in premanifest HDEGC. In the early manifest HDEGC, they also found significant atrophy in the thalamus, occipital and frontal cortex, and whole gray matter [57].…”
Section: Volumetric Mrimentioning
confidence: 96%
“…The progressive degeneration of cortico-striatal circuits and synaptic dysfunction and loss 7 , 8 in Huntington’s disease may induce changes to frequency-specific activities through several mechanisms. EEG activity may change as a direct consequence of the loss of contributing synapses and circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic dysfunction and loss 7 , 8 and progressive neurodegeneration in Huntington’s disease may lead to changes in brain oscillatory activity as assessed with EEG. 9 In particular, a decrease in synchronized neuronal activity with specific spectral patterns such as reductions in power in the classical alpha (α) band and at the theta-alpha (θ/α) border (7–8 Hz) has been reported in premanifest and early-manifest Huntington’s disease.…”
Section: Introductionmentioning
confidence: 99%